Design of an interface heating device based on polydivinylbenzene/SiO2/Bi2WO6 and its visible light response performance for water purification. Issue 5 (23rd January 2023) - Miao, Xiao; Zhao, Ling; Ren, Guina; Pang, Yunlong; Xin, Hui; Ge, Bo; Liu, Cancan
Abstract : Polydivinylbenzene/SiO2 /Bi2 WO6 coatings with low surface energy are the guarantee of devices floating, while the loaded Bi2 WO6 can absorb the light energy to degrade the pollutants dissolved in the water. Abstract : Environmental pollution and the shortage of drinking water are the challenges that mankind is facing. Solar interface evaporation technology has been demonstrated as an important method for producing clean water, but its application to sewage still faces problems, mainly manifested in solubility and oily pollutants. Therefore, an evaporator device contains a superhydrophobic Bi2 WO6 felt floating layer, a filter paper hydrophilic layer, and a copper foam/CuO photothermal layer, of which the water contact angle of the superhydrophobic felt can reach 159°. The floating layer not only has the ability to adsorb n -hexane but the Rh B degradation can also be realized under indoor/outdoor light conditions. The carrier life of Bi2 WO6 is 28.8 ns. A copper foam/CuO photothermal layer prepared through a low-temperature treatment is combined with the floating and hydrophilic layer to obtain an evaporation rate of 1.53 kg m −2 h −1 .